Sustained neutrophil extracellular traps cause fracture nonunion - Weixin Xie; Lilly-Charlotte Albertsen; Gesine Eis-Janzyk; Charlotte Kühlwein; Shan Jiang; Carsten Schlickewei; Holger Kleinertz; Ruben Augustin; Jan Sevecke; Saskia Schröder; Mayla Rickert; Samira Weisselberg; et al. (Science Translational Medicine, 2026)
Fracture healing is an evolutionarily conserved process that depends on the complex interplay of osteogenic, angiogenic, and inflammatory responses. Impaired bone healing is observed in up to 10 to 15% of patients with fractures and can lead to nonunion, which is the absence of bone healing. Here, we explore a role of neutrophil extracellular traps (NETs) in fracture healing and their association with nonunion. In both mice and humans, skeletal injury triggers rapid but transient NET formation at the fracture site. The combined genetic deletion of enzymes essential for NET clearance, DNase1 and DNase1-like-3 , initially favors callus mineralization in the early healing phase. However, sustained NET elevation subsequently leads to impaired bone regeneration and fracture nonunion over the course of healing. Conversely, additional deletion of the NET-generating enzyme Pad4 improves bone regeneration and lowers nonunion rates. Mechanistically, NETs up-regulate cGas-Sting signaling, thereby collapsing the formation of type-H vessels, which couple osteogenesis to angiogenesis in the fracture callus. Pharmacological inhibition of cGas-Sting restored type-H vessels, enhanced bone healing, and prevented nonunion in DNase -deficient but not Pad4 -deficient mice. In patients, serum NET markers declined during normal healing but were elevated in nonunion, correlating with excessive NET and STING accumulation in the callus. Therapeutically, the inhibition of NET formation with the Pad4 inhibitor GSK484 or the promotion of NET clearance with dornase alfa (recombinant DNase1) accelerated bone repair and prevented nonunion in preclinical models. These findings identify sustained NETs as a disruptor of fracture healing and a potential target for enhancing bone regeneration.